2009
DOI: 10.1002/clen.200900021
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Assessment by Microtox® in Sediments, Pore Waters and Sediment Saline Elutriates in the Gulf of Gdansk (Baltic Sea)

Abstract: The toxicity of sediments in the Gulf of Gdansk is analyzed in relation to the chemical composition of interstitial and near-bottom waters, and sediment properties. The toxicity of sediments, pore waters and saline elutriates is determined by using the Microtoxm test based on changes in light production of the luminescent bacteria Vibrio fischeri. The results indicate considerable toxicity in the majority of examined sediments. Since the sediment elutriates and pore waters are toxic in some cases, the total to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 38 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…Ammonia concentration in the pore water was not analyzed in the study. However, in other papers it has been found that pore water ammonia concentrations can be inhibitory to test organisms (Phillips et al 2005 ; Rosen et al 2008 ; Łukawska-Matuszewska et al 2009 ). Other studies have found that the Microtox ® test is an inadequate indicator of ammonia toxicity since it is not very sensitive to ammonia (Rosen et al 2008 ).…”
Section: Discussionmentioning
confidence: 94%
“…Ammonia concentration in the pore water was not analyzed in the study. However, in other papers it has been found that pore water ammonia concentrations can be inhibitory to test organisms (Phillips et al 2005 ; Rosen et al 2008 ; Łukawska-Matuszewska et al 2009 ). Other studies have found that the Microtox ® test is an inadequate indicator of ammonia toxicity since it is not very sensitive to ammonia (Rosen et al 2008 ).…”
Section: Discussionmentioning
confidence: 94%
“…This strain of the organism can be used to evaluate both acute and chronic toxicity as it is sensitive to a broad range of chemicals (organic, trace metals and organo-metals) and used in studies of riverine, estuarine and marine sediments from Europe, North and Central America. 19,[40][41][42][43] The EC 50 proles (i.e. 50% decrease in light output) show that sediments in cores A, B and D are non-toxic to moderately toxic whereas all core C intervals were non-toxic ( Fig.…”
Section: Sediment Toxicity Screeningmentioning
confidence: 99%
“…The results of toxicity of the bottom sediment from the Port of Gdansk and the Gulf of Gdansk (Niemirycz et al 2007, Łukawska-Matuszewska et al 2009, Niemirycz & Jankowska 2011 measured using Microtox® are presented in Table 8.…”
Section: Rangementioning
confidence: 99%